Системы поддержки принятия решений в управлении проектами, основанные на качественных методах - Гуца, Олег Николаевич; Ельчанинов, Дмитрий Борисович; Порван, Андрей Павлович; Якубовская, София Владимировна (НТУ "ХПИ", 2017)
Существующие системы поддержки принятия решений в управлении проектами имеют в своей основе преимущественно количественные методы с присущими им недостатками. Предложена информационная технология создания систем поддержки принятия решений на основе качественных методов вербального анализа, а именно метода ординарной классификации с доработками авторов. Показана реализация предложенной технологии на примере создания системы оценки вероятной успешности проекта на ранних стадиях выполнения в виде web-приложения.

State-of-the-art decision support systems (DSS) used in project management are mainly based on quantitative methods. However, formal methods of modern mathematics alone are not capable of being a universal means of solving all practical problems in this area. Due to their limited capabilities and lack of statistical and other relevant information, economic-mathematical methods find limited application in management and marketing. In addition, there are few reliable validation and verification methods available. On the other hand, expert assessment methods are free of these disadvantages and are almost the only way to solve this type of problem. Advantages of this approach include simplicity of prediction in nearly every case, and excellent performance in incomplete information scenarios. This work presents a new information technology which generates a DSS, based on qualitative methods of verbal decision analysis. The authors propose certain modifications to the method of ordinary classification. The proposed technology is implemented as a web-application, which is used to design a system that evaluates the probability of a successful project.
Decision support systems based on qualitative methods for project management
Keywords: информационная технология; вербальный анализ; качественные методы; ординарная классификация; принятие решений; система поддержки; управление проектами; information technology; decision support system; ordinary classification; project management; verbal analysis; qualitative methods